An empirical study on consumer purchase intention for nuts and influencing factors—Survey based on consumers from Zhejiang. (November 2020) - Hong, Lin; Yao, Linna; Xie, Pian; Li, Weixia
Abstract: Recently, the global demand for nuts has increased, which has brought considerable economic benefits. However, specific hygiene issues have affected the development of the nut market. Accordingly, it is necessary to investigate consumer purchase intention in this regard. Hitherto, no in-depth research has been done about the nut industry. Thus, the present study analyzed consumers' willingness to purchase nuts and the influencing factors through logistic regression analysis and a structural equation model. We found that product attribute evaluation variables had a significant positive effect on consumers' willingness to purchase nuts. Producers of nuts should place greater emphasis on product improvement. Our conclusions can serve as a reference for formulating an industrial development strategy. Highlights: Logistic regression analysis of consumers' willingness to purchase nuts. The structural equation model of the influencing factors for consumers to purchase nuts is established. Product attribute has a significant positive impact on consume s' willingness to buy nuts. Producers should place greater emphasis on product improvement.